Multimodality Imaging in Cardiac Amyloidosis: State‐of‐the‐Art Review - Timóteo, AT (2022)
Amyloidosis is a systemic disease, characterized by deposition of amyloid fibrils in various organs, including the heart. For the diagnosis of cardiac amyloidosis (CA) it is required a high level of clinical suspicion and in the presence of clinical, laboratorial, and electrocardiographic red flags, a comprehensive multimodality imaging evaluation is warranted, including echocardiography, magnetic resonance, scintigraphy, and computed tomography, that will confirm diagnosis and define the CA subtype, which is of the utmost importance to plan a treatment strategy. We will review the use of multimodality imaging in the evaluation of CA, including the latest applications, and a practical flow-chart will sum-up this evidence.